Educational leadership and music : lessons for tomorrow's school leaders - Watson, Terri N.; Brooks, Jeffrey S., 1970-; Beachum, Floyd D. (New directions in educational leadership (Charlotte, N.C.), 2017)
In this book we considered new territory for educational leadership by looking to music for lessons and inspiration that may inform the next generation of schools leaders. Each chapter focuses on an artist or group whose work serves to refine, extend, and challenge our thinking in regards to educational leadership. You will find a vast array of musical forms of expression analyzed and described by an equally diverse collection of educational leadership scholars and practitioners. There may be some who question the academic appropriateness or relevance of a text such as this one. Our response is that part of our ongoing mission should be to break ourselves out of academic silos and forge meaningful connections between seemingly disparate disciplines. Furthermore, educational leadership stands to gain more by drawing from the arts and specifically musical influences. Finally, music is an obvious part of most of our lives; why not explore the ways in which it impacts us on an academic level and not just a personal level? In sum, we ask that as you read the chapters of this book, you reflect on your own musical tastes and favorite artists.